2014
DOI: 10.1155/2014/902315
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular View of Autophagy in Lepidoptera

Abstract: Metamorphosis represents a critical phase in the development of holometabolous insects, during which the larval body is completely reorganized: in fact, most of the larval organs undergo remodeling or completely degenerate before the final structure of the adult insect is rebuilt. In the past, increasing evidence emerged concerning the intervention of autophagy and apoptosis in the cell death processes that occur in larval organs of Lepidoptera during metamorphosis, but a molecular characterization of these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 102 publications
(158 reference statements)
2
43
0
2
Order By: Relevance
“…However, three types are best known: apoptosis, necrosis and autophagy. They are common processes that occur in the digestive epithelia of invertebrates (Malagoli et al 2010; Franzetti et al 2012; Romanelli et al 2014, 2016; Wilczek et al 2014; Lipovšek and Novak 2015; Rost-Roszkowska et al 2015, 2016; Sonakowska et al 2016). When the cytoplasm is rich in autophagic structures, apoptosis and/or necrosis is activated (Levine and Yuan 2005; Giusti et al 2007; Tettamanti et al 2007; Rost-Roszkowska et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, three types are best known: apoptosis, necrosis and autophagy. They are common processes that occur in the digestive epithelia of invertebrates (Malagoli et al 2010; Franzetti et al 2012; Romanelli et al 2014, 2016; Wilczek et al 2014; Lipovšek and Novak 2015; Rost-Roszkowska et al 2015, 2016; Sonakowska et al 2016). When the cytoplasm is rich in autophagic structures, apoptosis and/or necrosis is activated (Levine and Yuan 2005; Giusti et al 2007; Tettamanti et al 2007; Rost-Roszkowska et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Mitophagy is a type of selected autophagy in which mainly damaged or non-active mitochondria are neutralized and discharged from the cytoplasm (Włodarczyk et al 2017). Selective autophagy, in contrast to a non-selective process, forces the specific structures or organelles into the autophagosomes to cause them to be eventually digested (Mijaljica et al 2012; Shaid et al 2013; Romanelli et al 2014, 2016). Depending on the organelles that are enclosed inside autophagosomes, we can distinguish mitophagy, reticulophagy, lipophagy, nucleophagy, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that macroautophagy plays a central role in remodeling organs in Diptera (mosquito and fruit fly; Coppens, 2011;Tracy and Baehrecke, 2013), Lepidoptera (silkworm; Goncu and Parlak, 2008;Franzetti et al, 2012;Romanelli et al, 2014) and Hymenoptera (honey bee; Silva-Zacarin et al, 2008;Santos et al, 2015). However, it is not clear whether CMA is also involved in the remodeling process.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence has prompted the hypothesis of a causative role of autophagy in the demise of these tissues, although the existence of autophagic cell death in these insects has never been clearly and definitively demonstrated2128.…”
mentioning
confidence: 99%